1990
DOI: 10.1093/bja/65.3.373
|View full text |Cite
|
Sign up to set email alerts
|

Effect of General Anaesthesia on Whole Body Protein Turnover in Patients Undergoing Elective Surgery

Abstract: To determine if general anaesthesia alone or in conjunction with surgery alters body protein turnover, we studied six healthy, unpremedicated females undergoing elective total abdominal hysterectomy. Changes in protein metabolism, synthesis and breakdown were estimated by an isotope dilution technique using a continuous infusion of the stable isotope tracer, L-[1-13C]leucine, before anaesthesia (4 h), during anaesthesia alone (1 h), during anaesthesia and surgery (1 h) and in the recovery period (2 h). General… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…31 Although the exact location of the observed surgery induced upregulation of whole body protein turnover remains unclear, it is likely that the increased protein breakdown is taking place in the splanchnic as well as in the muscle compartment. A previous study in unpremedicated females undergoing elective total abdominal hysterectomy 25 showed that whole body protein breakdown did not change with general anaesthesia but decreased with both surgery and anaesthesia, and during the acute recovery period. It remains unclear whether the combination of multiple factors (including medication, starvation, anaesthesia, trauma , after intake of the high protein supplement.…”
Section: Metabolic Effects Of Breast Surgerymentioning
confidence: 82%
See 1 more Smart Citation
“…31 Although the exact location of the observed surgery induced upregulation of whole body protein turnover remains unclear, it is likely that the increased protein breakdown is taking place in the splanchnic as well as in the muscle compartment. A previous study in unpremedicated females undergoing elective total abdominal hysterectomy 25 showed that whole body protein breakdown did not change with general anaesthesia but decreased with both surgery and anaesthesia, and during the acute recovery period. It remains unclear whether the combination of multiple factors (including medication, starvation, anaesthesia, trauma , after intake of the high protein supplement.…”
Section: Metabolic Effects Of Breast Surgerymentioning
confidence: 82%
“…muscle) are mobilized . Previously, decreased, increased, and unchanged protein breakdown rates were observed after surgery, likely due to variations in the extent of trauma, postoperative phase (early or late), and methods used to quantify protein breakdown. A previous study found increased albumin synthesis levels after major abdominal surgery .…”
Section: Discussionmentioning
confidence: 99%
“…Clonidine has been shown to blunt this effect as well, likely through an increase in norepinephrine, activating descending spinal pathways and directly blocking ACTH secretion 9 . General anesthetics, without opioids or benzodiazepines, have not been found to be effective at blunting the surgical stress response 10,11 . These findings have led to the routine use of opioids with general anesthesia and the frequent use of local and epidural anesthesia.…”
Section: The Surgical Stress Responsementioning
confidence: 99%
“…Lattermann et al (23) detected catabolism by a decline in protein synthesis and an increase in amino acid oxidation within the first two hours following surgery, in patients who underwent colectomy. In another study, Carli et al (24) pointed to decreased protein catabolism intraoperatively and in the first 2 hours postoperatively. Increase in urinary nitrogen levels and negative nitrogen balance can be detected at an early stage after injury peaking at day 7.…”
Section: Protein and Amino Acid Metabolismmentioning
confidence: 94%